アデリーペンギン ノ キュウエ コウドウ ニ ツイテ ノ イチ コウサツ - 青柳, 昌宏; アオヤナギ, マサヒロ; 田宮, 康臣; タミヤ, ヤスオミ; Aoyanagi, Masahiro; Tamiya, Yasuomi (1983)
P(論文) クレイシ中期にアデリーペンギンの給餌行動を, 24時間連続観察し, 以下の4点についてまとめた。1) 雛が給餌される頻度, 2) 給餌のため, 親鳥がコロニーに帰る頻度, 3) 雛が出てしまった空巣を含むなわばりの識別と利用, 4) 雛の生存率と育雛行動の雛数によるちがい。 The feeding behavior of Adelie Penguin Pygoscelis adeliae was observed from morning till night during the middle creche stage, and data about the following items were obtained : 1) feeding frequency of chicks, 2) returning frequency of parents, 3) recognition and utilization of the abandoned nesting territories, and 4) difference of survival rate of chicks and parental care due to brood size. departmental bulletin paper